REVIU SERTA OPTIMASI DESAIN KAPAL NELAYAN PUGER DITINJAU ASPEK UKURAN DAN STABILITAS - Gusma Hamdana Putra; Neilani Fanisa Putri Arifina (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Optimal fishing vessel facilities must support the high potential of fisheries in Jember’s Puger waters to obtain maximum results. This research discusses ship design analysis and ship design optimization for Puger waters. Design analysis related to the primary size and stability of the ship is an aspect of this research. Existing ship design modelling was carried out using the Gross Tonnage approach and secondary data. The results show that the primary size ratio, GT calculation, and stability still need to meet the criteria. Optimization in an alternative design produces a primary size ratio of length, width, height, and draft, namely 18 x 4.4 x 2 x 1.6 meters, and a GT calculation that suits field conditions, namely 20GT. Stability analysis of three load conditions in alternative designs complies with the BKI Guidelines on Intact Stability Special Criteria of Ship Fishing Vessels.